Exploring Learning Styles and Their Variations Through Diagnostic Assessment in Addressing Students’ Learning Needs - Widiastuti, Anik; Azizah, Primanisa Inayati; MR, Moh. Irsyad Fahmi; Septiantoko, Riko; Prawoto, Sri Bagus Wahyu; Hartati, Putri Ria Indah; Febriani, Putri (Publikasi Berkala Pendidikan Ilmu Sosial, 2026)
This research aims to analyze learning styles and their varieties through diagnostic assessment to meet students' learning needs. The method used in this research is a descriptive quantitative method, with a sample of 27 8th-grade students at SMPN 9 Yogyakarta. The research instruments include the learning style questionnaire, observation, and interview. The results showed that students have three main learning styles, namely visual (40%), auditory (35%), and kinesthetic (25%). In addition, there are combinations of learning styles such as visual-auditory (18%), visual-kinesthetic (13%), and auditory-kinesthetic (13%). These findings suggest that learning approaches should be tailored to learners' individual learning preferences to enhance learning effectiveness. By implementing diagnostic assessments, teachers can design learning strategies that are more inclusive and better suited to learners' needs, thereby positively impacting their motivation and learning achievement.